2019
DOI: 10.18593/abh.19701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in vitro of antimicrobial activity of tucumã oil (Astrocaryum Vulgare)

Abstract: Hospital Infection is a major health problem and affects around 1.5 million people annually around the world. The Amazon region has a wide diversity of native palm trees that have fruits and oilseeds. Astrocaryum vulgare, commonly known as Tucumã in Brazil, belongs to the family Arecaceae. This palm has orange, fleshy, single-egg-shaped fruits that are used for therapeutic purposes in diseases of the eyes and skin due to the high content of carotenoids, oil is used in cooking, health treatment and massage. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
8
0
2
Order By: Relevance
“…The reason for the lack of antagonism in Kitahara et al 47 and Hess et al 57 could be the concentration of LA used in the study, which probably did not reach a sufficient value for the antagonism to be exerted. There is no information on the interaction of palm oils rich in MCFAs as their antibacterial activity was not confirmed in the study 54 , 58 because hydrolysis of oils was not performed 26 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The reason for the lack of antagonism in Kitahara et al 47 and Hess et al 57 could be the concentration of LA used in the study, which probably did not reach a sufficient value for the antagonism to be exerted. There is no information on the interaction of palm oils rich in MCFAs as their antibacterial activity was not confirmed in the study 54 , 58 because hydrolysis of oils was not performed 26 .…”
Section: Discussionmentioning
confidence: 92%
“…This result is the opposite of that observed in this study, where the oils acted as an antibacterial only after being hydrolyzed by the porcine pancreatic lipase. Rossato et al 54 also observed no antistaphylococcal activity of unhydrolyzed A. vulgare oil. Results of in vitro screening of C. nucifera oil and other MCFA-containing fats, with lipolytic enzymes that simulated gastric conditions in piglets, showed a significant change in suppression of gut microbiota (total anaerobes and E. coli ) 55 .…”
Section: Discussionmentioning
confidence: 96%
“…The search for new effective antibacterial materials is significant for combating drug resistance, and NPs are being established as a promising approach to solving this problem (WANG et al, 2017). Rossato et al (2019) showed that Tucumã-free oil showed antimicrobial activity against 5 microorganisms. A.vulgare oil is rich in lipids, carotenes, fibers and tocopherol, providing the fruit with high energy and nutritive content.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the antimicrobial effect of Tucumã oil may be associated with its chemical composition, which includes several types of polyphenol molecules and fatty acids. Still, according to Rossato et al (2019) polyphenols are secondary metabolites produced by higher plants, which play several essential roles in the physiology of plants that have potential healthy properties in the human body, mainly as antioxidants, anti-inflammatories, anti-allergens, and antimicrobials. This suggests that low uptake of free oil may limit its effectiveness, and that lipid encapsulation can help the active ingredients achieve their goals.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of GO and rGO was evaluated by the technique of microdilution in the broth that determines the minimum inhibitory concentration (MIC) capable of causing inhibition of visible bacterial growth. This technique was performed according to Rossato et al (2019), based on protocol M07-A8 of the Clinical & Laboratory Standards Institute (CLSI). Clinical isolates of Pseudomonas aeruginosa (P. aeruginosa), Streptococcus agalactiae (S. agalactiae), and Multiple-resistant Staphylococcus aureus (MRSA) from the Santa Maria University Hospital -RS, previously identified by specific phenotypic methods, were used.…”
Section: Antimicrobial and Antibiofilm Activitiesmentioning
confidence: 99%